Estrogen and Estrogen Receptor Modulators: Potential Therapeutic Strategies for COVID-19 and Breast Cancer - Hu, Shuying; Yin, Feiying; Nie, Litao; Wang, Yuqin; Qin, Jian; Chen, Jian (Frontiers in Endocrinology, 2022)
Owing to the ongoing coronavirus disease 2019 (COVID-19) pandemic, we need to pay a particular focus on the impact of coronavirus infection on breast cancer patients. Approximately 70% of breast cancer patients express estrogen receptor (ER), and intervention therapy for ER has been the primary treatment strategy to prevent the development and metastasis of breast cancer. Recent studies have suggested that selective estrogen receptor modulators (SERMs) are a potential therapeutic strategy for COVID-19. With its anti-ER and anti-viral combined functions, SERMs may be an effective treatment for COVID-19 in patients with breast cancer. In this review, we explore the latent effect of SERMs, especially tamoxifen, and the mechanism between ER and virus susceptibility.